(Photo-)crosslinkable gelatin derivatives for biofabrication applications. (1st October 2019) - Van Hoorick, Jasper; Tytgat, Liesbeth; Dobos, Agnes; Ottevaere, Heidi; Van Erps, Jürgen; Thienpont, Hugo; Ovsianikov, Aleksandr; Dubruel, Peter; Van Vlierberghe, Sandra
Graphical abstract: Abstract: Over the recent decades gelatin has proven to be very suitable as an extracellular matrix mimic for biofabrication and tissue engineering applications. However, gelatin is prone to dissolution at typical cell culture conditions and is therefore often chemically modified to introduce (photo-)crosslinkable functionalities. These modifications allow to tune the material properties of gelatin, making it suitable for a wide range of biofabrication techniques both as a bioink and as a biomaterial ink (component). The present review provides a non-exhaustive overview of the different reported gelatin modification strategies to yield crosslinkable materials that can be used to form hydrogels suitable for biofabrication applications. The different crosslinking chemistries are discussed and classified according to their mechanism including chain-growth and step-growth polymerization. The step-growth polymerization mechanisms are further classified based on the specific chemistry including different (photo-)click chemistries and reversible systems. The benefits and drawbacks of each chemistry are also briefly discussed. Furthermore, focus is placed on different biofabrication strategies using either inkjet, deposition or light-based additive manufacturing techniques, and the applications of the obtained 3D constructs. Statement of Significance: Gelatin and more specifically gelatin-methacryloyl has emerged to become one of the gold standard materials as an extracellular matrix mimic in the field of biofabrication. However, also other modification strategies have been elaborated to take advantage of a plethora of crosslinking chemistries. Therefore, a review paper focusing on the different modification strategies and processing of gelatin is presented. Particular attention is paid to the underlying chemistry along with the benefits and drawbacks of each type of crosslinking chemistry. The different strategies were classified based on their basic crosslinking mechanism including chain- or step-growth polymerization. Within the step-growth classification, a further distinction is made between click chemistries as well as other strategies. The influence of these modifications on the physical gelation and processing conditions including mechanical properties is presented. Additionally, substantial attention is put to the applied photoinitiators and the different biofabrication technologies including inkjet, deposition or light-based technologies.